Acculturation of French fashion in Japan after World War II: Fashion as a device constructing identity - Koma, Kyoko (Acta Orientalia Vilnensia, 2011)
Vytautas Magnus University / Mykolas Romeris University In our paper, we discuss how French fashion was acculturated in Japan after WWII, a period in which Japan rushed to modernise/occidentalise. Through an analysis of the dominant discourse of Japanese fashion magazines, we focus on the following French fashion trend that spread throughout Japan: a long, flared skirt inspired by a Paris fashion. The skirt was a new look by French fashion designer Christian Dior just after WWII. The other focus of this paper is on the soaring popularity of European brand Louis Vuitton in 1970 and 1999. Modernisation in the fashion realm following WWII could be said to be the localisation of the French fashions followed by Americans; the manner by which French fashion was acculturated in Japan after WWII changed according to the Japanese social context. Articles in the dressmaking fashion magazine Soen promoted the new style blindly. In the 1970s when great economic growth was realised, Japanese travellers shopping for real Louis Vuitton bags in France were attempting to belong to middle class society. Featured articles on Louis Vuitton in 1999 presented several ways of localising the usage of this bag for all generations of women to find belonging in their own groups.